Emerging lanthanum (III)-containing materials for phosphate removal from water: A review towards future developments. (December 2020) - Zhi, Yue; Zhang, Chuhui; Hjorth, Rune; Baun, Anders; Duckworth, Owen W.; Call, Douglas F.; Knappe, Detlef R.U.; Jones, Jacob L.; Grieger, Khara
Highlights: LM strongly bind phosphate under diverse environmental conditions. Phosphate uptake capacity of LM is strongly correlated with their La content. Phosphate uptake kinetics are influenced by LM formulation and water chemistry. La release from LM into water can occur under some environmental conditions. Ecological monitoring and long-term exposure studies are needed in future research. Abstract: The last two decades have seen a rise in the development of lanthanum (III)-containing materials (LM) for controlling phosphate in the aquatic environment. >70 papers have been published on this topic in the peer-reviewed literature, but mechanisms of phosphate removal by LM as well as potential environmental impacts of LM remain unclear. In this review, we summarize peer-reviewed scientific articles on the development and use of 80 different types of LM in terms of prospective benefits, potential ecological impacts, and research needs. We find that the main benefits of LM for phosphate removal are their ability to strongly bind phosphate under diverse environmental conditions (e.g., over a wide pH range, in the presence of diverse aqueous constituents). The maximum phosphate uptake capacity of LM correlates primarily with the La content of LM, whereas reaction kinetics are influenced by LM formulation and ambient environmental conditions (e.g., pH, presence of co-existing ions, ligands, organic matter). Increased La solubilization can occur under some environmental conditions, including at moderately acidic pH values (i.e., < 4.5–5.6), highly saline conditions, and in the presence of organic matter. At the same time, dissolved La will likely undergo hydrolysis, bind to organic matter, and combine with phosphate to precipitate rhabdophane (LaPO4 ·H2 O), all of which reduce the bioavailability of La in aquatic environments. Overall, LM use presents a low risk of adverse effects in water with pH > 7 and moderate-to-high bicarbonate alkalinity, although caution should be applied when considering LM use in aquatic systems with acidic pH values and low bicarbonate alkalinity. Moving forward, we recommend additional research dedicated to understanding La release from LM under diverse environmental conditions as well as long-term exposures on ecological organisms, particularly primary producers and benthic organisms. Further, site-specific monitoring could be useful for evaluating potential impacts of LM on both biotic and abiotic systems post-application.